Streptococcus pyogenes and re-emergence of scarlet fever as a public health problem - Samson SY Wong; Kwok-Yung Yuen (Emerging Microbes and Infections, 2012)
Explosive outbreaks of infectious diseases occasionally occur without immediately obvious epidemiological or microbiological explanations. Plague, cholera and Streptococcus pyogenes infection are some of the epidemic-prone bacterial infections. Besides epidemiological and conventional microbiological methods, the next-generation gene sequencing technology permits prompt detection of genomic and transcriptomic profiles associated with invasive phenotypes. Horizontal gene transfer due to mobile genetic elements carrying virulence factors and antimicrobial resistance, or mutations associated with the two component CovRS operon are important bacterial factors conferring survival advantage or invasiveness. The high incidence of scarlet fever in children less than 10 years old suggests that the lack of protective immunity is an important host factor. A high population density, overcrowded living environment and a low yearly rainfall are environmental factors contributing to outbreak development. Inappropriate antibiotic use is not only ineffective for treatment, but may actually drive an epidemic caused by drug-resistant strains and worsen patient outcomes by increasing the bacterial density at the site of infection and inducing toxin production. Surveillance of severe S. pyogenes infection is important because it can complicate concurrent chickenpox and influenza. Concomitant outbreaks of these two latter infections with a highly virulent and drug-resistant S. pyogenes strain can be disastrous.